Better Alone? Evidence on the Costs of Intermunicipal Cooperation - Clémence Tricaud (Center for Economic Studies and Ifo Institute (CESifo), 2021)
While central governments encourage intermunicipal cooperation to achieve economies of scale, municipalities are often reluctant to integrate. This paper provides new evidence on the factors explaining their resistance by exploiting a 2010 reform in France that forced non-integrated municipalities to enter an intermunicipal community. Using a difference-in-differences strategy, I assess the causal impact of integration on resisting municipalities. Comparing their experience to that of municipalities that had chosen to integrate before the law, I can identify the local consequences explaining why resisting municipalities opposed integration in the first place. I first find that municipalities forced to integrate experienced a 12.5-percent increase in the number of building permits delivered per year. This impact is driven by high-demand urban municipalities, consistent with NIMBYism explaining their resistance to integration. Second, I find that rural municipalities ended up with fewer local public services. I do not find the same effects for municipalities that voluntarily integrated, while I show that both types of municipality enjoyed similar benefits of integration, in terms of better access to public transport and higher fiscal revenues. These findings support the fact that municipalities resisted to avoid the local costs of integration.
Keywords: H70; R52; R53; 330; local governments; intermunicipal cooperation; difference-in-differences; housing regulations; local public services